Micro-cutting of biocomplatible materials used for medical applications - Kushendarsyah, Saptaji (2017)
Micro-end milling is one of the promising methods for rapid fabrication of features with 3D complex shapes. However, controlling the micro-end milling process to obtain the desired results is more challenging compared to that of macro-end milling due to the size effect and uncontrollable factors such as vibrations, burrs and tool breakage. The problem is much pronounced when workpiece material is a difficult-to-process material such as titanium-based alloys which are widely used as material of choice for medical implants. The objective of this research is to study the micro milling of selected bio-compatible materials which in this case is titanium alloys. The study is focused mainly on the experimental work on the effect of machining parameters especially feed rate and depth of cut with constant spindle speed in wet and dry condition on Ti-6Al-4V's surface roughness using micro-milling process. This experiment was design using Design of Experiment (DOE) method and few numbers of experiments were constructed. The result from this research can be applied in the production of the biomedical implants especially those consist of micro-scale features. The implants are being used in many different parts of the body for various applications such as orthopedics, pacemakers, cardiovascular stents, neural prosthetics or drug delivery system. The results show that feed rate is the most critical parameter which effect on surface roughness during machining process followed by depth of cut. Dry condition shows better surface quality compared to wet condition.